2012
DOI: 10.1016/j.visres.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of selective attention in action video game players

Abstract: Over the past few years, the very act of playing action video games has been shown to enhance several different aspects of visual selective attention. Yet little is known about the neural mechanisms that mediate such attentional benefits. A review of the aspects of attention enhanced in action game players suggests there are changes in the mechanisms that control attention allocation and its efficiency (Hubert-Wallander et al., 2010). The present study used brain imaging to test this hypothesis by comparing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
201
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(240 citation statements)
references
References 76 publications
17
201
0
6
Order By: Relevance
“…Interestingly, cognitive neuroscience has shown that the brain bases of skilled performance in these two groups are not so different: both experienced pilots and trained/experienced gamers show evidence of greater neural efficiency when operating simulated aviation tasks and playing first-person action games, respectively. Bavelier et al (2011), as discussed above, showed that as task attentional demands increased, skilled gamers showed less activation in a network of task-related areas (superior frontal sulcus, middle frontal gyrus, inferior frontal gyrus, cingulum, and intraparietal sulcus) in comparison to non-gamers. Peres et al (2000), in a study of novice and experienced pilots showed that with increasing task difficulty (increasing airspeed), expert pilots showed reduced activity in visual and motor centers of the brain.…”
Section: The Brain Bases Of Improvement: What Changes After Multitaskmentioning
confidence: 74%
See 3 more Smart Citations
“…Interestingly, cognitive neuroscience has shown that the brain bases of skilled performance in these two groups are not so different: both experienced pilots and trained/experienced gamers show evidence of greater neural efficiency when operating simulated aviation tasks and playing first-person action games, respectively. Bavelier et al (2011), as discussed above, showed that as task attentional demands increased, skilled gamers showed less activation in a network of task-related areas (superior frontal sulcus, middle frontal gyrus, inferior frontal gyrus, cingulum, and intraparietal sulcus) in comparison to non-gamers. Peres et al (2000), in a study of novice and experienced pilots showed that with increasing task difficulty (increasing airspeed), expert pilots showed reduced activity in visual and motor centers of the brain.…”
Section: The Brain Bases Of Improvement: What Changes After Multitaskmentioning
confidence: 74%
“…The attractive and positive features of videogaming with its inherent multitasking may provide a foundation for developing new instructional techniques. Bavelier et al (2011) identified the neural bases of improved selective attention in action videogame players, indicating which processes became more efficient. As distracters and attentional demands increased, skilled gamers showed less activation of visual areas and of a frontal-parietal network of areas (superior frontal sulcus, middle frontal gyrus, inferior frontal gyrus, cingulum, and intraparietal sulcus) in comparison to nongamers.…”
Section: Videogame Training and Practice: Improvement In Selective Atmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiences as varied as driving a taxi cab, playing a musical instrument, physical exercise, or playing video games change the brain both functionally and structurally (e.g. Bavelier, Achtman, Mani, & Föcker, 2012;Erickson et al, 2011;Herholz & Zatorre, 2012;Maguire et al, 2000). In this context, it should come as no surprise that a life in two languages would do the same.…”
mentioning
confidence: 99%